P.P.T and Areas!

Geometry Level pending

Let p p be prime and p > 2 p > 2 .

In A B C , A B = p 2 4 , A C = 4 p , B C = p 2 + 4 , M \triangle{ABC}, \overline{AB} = p^2 - 4, \overline{AC} = 4p, \overline{BC} = p^2 + 4, M is a midpoint of B C \overline{BC} and A M \overline{AM} is a side of square M A E D MAED and M D \overline{MD} intersects A C \overline{AC} at F F .

If there exists a unique value of prime p > 2 p > 2 for which M D \overline{MD} intersects A C \overline{AC} at F F ( I . E ; (I.E; for which the above construction is possible), then enter the value of A A E D F A_{AEDF} or else enter 0 0 .


The answer is 33.4479166666666667.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

David Vreken
Feb 18, 2021

As long as A B < A C AB < AC , the M D MD will intersect A C AC . Therefore, p 2 4 < 4 p p^2 - 4 < 4p , which solves to 2 2 2 < p < 2 + 2 2 2 - 2\sqrt{2} < p < 2 + 2\sqrt{2} or 0.828 < p < 4.828 -0.828 < p < 4.828 , which makes p = 3 p = 3 the only possible prime number for p > 2 p > 2 .

If p = 3 p = 3 , then A B = p 2 4 = 3 2 4 = 5 AB = p^2 - 4 = 3^2 - 4 = 5 , A C = 4 p = 4 3 = 12 AC = 4p = 4 \cdot 3 = 12 , and B C = p 2 + 4 = 3 2 + 4 = 13 BC = p^2 + 4 = 3^2 + 4 = 13 .

Since 5 2 + 1 2 2 = 1 3 2 5^2 + 12^2 = 13^2 , A B C \triangle ABC is a right triangle, and by Thales's Theorem right A \angle A will lie on the circle that has B C BC as its diameter.

Since M M is the midpoint of B C BC , M M is the center of that circle, and M B = M A = M C = 13 2 MB = MA = MC = \cfrac{13}{2} , so A C M \triangle ACM is an isosceles triangle.

As two base angles of an isosceles triangle, M C A = M A C \angle MCA = \angle MAC , which means A M F C A B \triangle AMF \sim \triangle CAB by AA similarity.

Since A M F C A B \triangle AMF \sim \triangle CAB , M F = M A A B A C = 13 2 5 12 = 65 24 MF = MA \cdot \cfrac{AB}{AC} = \cfrac{13}{2} \cdot \cfrac{5}{12} = \cfrac{65}{24} .

Then A A E D F = A M A E D A A M F = A M 2 1 2 M F A M = ( 13 2 ) 2 1 2 65 24 13 2 = 3211 96 33.4479 A_{AEDF} = A_{MAED} - A_{\triangle AMF} = AM^2 - \cfrac{1}{2} \cdot MF \cdot AM = \bigg(\cfrac{13}{2} \bigg)^2 - \cfrac{1}{2} \cdot \cfrac{65}{24} \cdot \cfrac{13}{2} = \cfrac{3211}{96} \approx \boxed{33.4479} .

Rocco Dalto
Feb 18, 2021

Let p > 2 p > 2 .

( p 2 4 , 4 p , p 2 + 4 ) (p^2 - 4, 4p, p^2 + 4) is a Pythagorean triple A B C \implies \triangle{ABC} is a right triangle with m A = 9 0 m\angle{A} = 90^{\circ} and cos ( θ ) = p 2 4 p 2 + 4 . \cos(\theta) = \dfrac{p^2 - 4}{p^2 + 4}.

Using the law of cosines on B A M \triangle{BAM} with included A B C = θ \angle{ABC} = \theta \implies

A M 2 = ( p 2 4 ) 2 + p 2 + 4 4 2 ( p 2 4 ) ( p 2 + 4 2 ) ( p 2 4 p 2 + 4 ) A M = p 2 + 4 4 \overline{AM}^2 = (p^2 - 4)^2 + \dfrac{p^2 + 4}{4} - 2(p^2 - 4)(\dfrac{p^2 + 4}{2})(\dfrac{p^2 - 4}{p^2 + 4}) \implies \overline{AM} = \dfrac{p^2 + 4}{4}

M F = A F cos ( θ ) = p 2 4 p 2 + 4 A F \implies MF = \overline{AF}\cos(\theta) = \dfrac{p^2 - 4}{p^2 + 4}\overline{AF} \implies ( p 2 + 4 ) 2 4 + ( p 2 4 ) 2 ( p 2 + 4 ) 2 A F 2 = A F 2 \dfrac{(p^2 + 4)^2}{4} + \dfrac{(p^2 - 4)^2}{(p^2 + 4)^2}\overline{AF}^2 = \overline{AF}^2

( p 2 + 4 ) 2 4 = 16 p 2 ( p 2 + 4 ) 2 A F 2 \implies \dfrac{(p^2 + 4)^2}{4} = \dfrac{16p^2}{(p^2 + 4)^2}\overline{AF}^2 \implies A F 2 = ( p 2 + 4 ) 4 64 p 2 A F = ( p 2 + 4 ) 2 8 p \overline{AF}^2 = \dfrac{(p^2 + 4)^4}{64p^2} \implies \overline{AF} = \dfrac{(p^2 + 4)^2}{8p}

M F = ( p 2 + 4 ) ( p 2 4 ) 8 p A A M F = \implies \overline{MF} = \dfrac{(p^2 + 4)(p^2 - 4)}{8p} \implies A_{\triangle{AMF}} = ( p 2 + 4 ) 2 ( p 2 4 ) 32 p \dfrac{(p^2 + 4)^2(p^2 - 4)}{32p} \implies

A A E D F = A R = A A E D M A A M F = ( p 2 + 4 ) 2 ( 8 p p 2 + 4 ) 32 p A_{AEDF} = A_{R} = A_{AEDM} - A_{\triangle{AMF}} = \dfrac{(p^2 + 4)^2(8p - p^2 + 4)}{32p} .

To show that there exists a unique prime value of p p that satisfies the above construction.

λ = 2 θ 9 0 m M F = tan ( 2 θ 9 0 ) = cos ( 2 θ ) sin ( 2 θ ) = sin 2 ( θ ) cos 2 ( θ ) 2 sin ( θ ) cos ( 2 θ ) = \lambda = 2\theta - 90^{\circ} \implies m_{MF} = \tan(2\theta - 90^{\circ}) = \dfrac{-\cos(2\theta)}{\sin(2\theta)} = \dfrac{\sin^2(\theta) - \cos^2(\theta)}{2\sin(\theta)\cos(2\theta)} =

( p 2 ) 2 ( 4 + 4 p p 2 ) 8 p ( p 2 4 ) > 0 \dfrac{(p - 2)^2(4 + 4p - p^2)}{8p(p^2 - 4)} > 0 and we already have p > 2 p > 2 \implies

p 2 4 p 4 < 0 p = 2 ( 2 + 1 ) = 4 ( 2 < p 4 ) p^2 - 4p - 4 < 0 \implies p = \lfloor{2(\sqrt{2} + 1)}\rfloor = 4 \implies (2 < p \leq 4)

\implies prime p = 3 A R = 3211 96 = 33.4479166666666667 p = 3 \implies A_{R} = \dfrac{3211}{96} = \boxed{33.4479166666666667} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...